Current pharmacological treatment options for male lower urinary tract symptoms. (June 2013) - Strittmatter, Frank; Gratzke, Christian; Stief, Christian G; Hedlund, Petter
<x xml:space="preserve">Abstract</x> Introduction: Benign prostatic hyperplasia (BPH) is a highly prevalent disease in the aging male and significantly impairs quality of life. Men with BPH present with lower urinary tract symptoms (LUTS), which include storage and voiding disorders. Medical therapy is the first option in patients with mild to moderate symptoms. Areas covered: α1-adrenoceptor antagonists, 5α-reductase inhibitors or the combination of both have been considered gold standard for pharmacological treatment over the last decade in this patient cohort. Recently, a variety of novel substances have been tested which include Phosphodiesterase Typ 5 inhibitors (PDE5i), anti-cholinergic agents and β-3-agonists. This article highlights the key studies with regard to each drug class and discusses current pharmacotherapy and possible future treatment options. Expert opinion: In patients with small prostates, α1-adrenoceptor antagonists represent the gold standard in the medical treatment of mild LUTS. For men with large prostate glands and mild to moderate LUTS, recent data support the combination of α1-adrenoceptor antagonists and 5α-reductase inhibitors. PDE5i may be useful in men with LUTS and concomitant erectile dysfunction, while anti-cholinergics have been shown to be beneficial in patients with predominant storage disorders. Future studies have to elucidate the role of β-3-agonists in men with BPH and LUTS.